2013
DOI: 10.1097/sla.0b013e3182683178
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled Surgery Admissions and Occupancy at a Children's Hospital

Abstract: Scheduled admissions contribute significantly to variability in occupancy. Predictable patterns of admissions lead to high occupancy on some days and unused capacity on others, with few days being at an optimal level of occupancy. These predictable patterns suggest opportunities to improve hospital operations with changes in scheduled admission patterns, which present a different problem than random demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The remainder of hospital admissions are elective scheduled admissions which, historically, have been scheduled early in the week to suit the needs of specialty practices that tend to follow a more regular schedule of working hours. In fact, studies from The Journal of Hospital Medicine and the Annals of Surgery have demonstrated that elective surgical admissions can vary by a factor of 3 between weekdays [49,50]. These large variations in elective admissions create a bottleneck early in the week, resulting in elective patients competing directly with ED patients for intensive care unit (ICU) and floor beds.…”
Section: Curesmentioning
confidence: 99%
“…The remainder of hospital admissions are elective scheduled admissions which, historically, have been scheduled early in the week to suit the needs of specialty practices that tend to follow a more regular schedule of working hours. In fact, studies from The Journal of Hospital Medicine and the Annals of Surgery have demonstrated that elective surgical admissions can vary by a factor of 3 between weekdays [49,50]. These large variations in elective admissions create a bottleneck early in the week, resulting in elective patients competing directly with ED patients for intensive care unit (ICU) and floor beds.…”
Section: Curesmentioning
confidence: 99%
“…Utilisation of intensive care resources needs to be balanced with the need to accommodate emergency referrals and the need to maintain the flow of planned patients through, and the utilisation of, operating theatres. Short-term fluctuations in demand for beds, for instance from current patient with longer lengths of stay or a surge in emergency referrals, can result in the cancellation of elective surgeries or refusals of emergency referrals due to lack of capacity [1][2][3][4]. One major constraint on capacity is the availability of specialised staff; if managers could have an early warning of busy periods, there might be scope to plan ahead [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Short-term fluctuations in demand for beds, for instance from current patient with longer lengths of stay or a surge in emergency referrals, can result in the cancellation of elective surgeries or refusals of emergency referrals due to lack of capacity [1][2][3][4]. One major constraint on capacity is the availability of specialised staff; if managers could have an early warning of busy periods, there might be scope to plan ahead [2,4]. It is also reasonable to suppose that there may be other, less tangible, benefits associated with staff being 'forewarned' of busy periods (see also Littig and Isken [5] and Chow [6]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation